PENERAPAN KEGIATAN YASIN DAN TAHLIL DALAM MENINGKATKAN NILAI NILAI RELIGIUS DI SEKOLAH SMPS AL-AMIN BENGKALIS - Azmi, Syahrul; Sugiarto, Wira (STAI Darul Qalam Tangerang, 2023)
This study raises the theme of the application of yasin and tahlil activities in increasing religious values. The aims of this research are: to find out the application of yasin and tahlil activities in increasing religious values ​​at SMPS Al-Amin Bengkalis, to find out the supporting factors and inhibiting factors. The subject of this research is the implementation of Yasin and Tahlil activities, and the object of this research is the students of SMPS Al-Amin Bengkalis. The sample in this study was 34 students from Bengkalis Al-Amin Middle School who took part in Yasin and Tahlil activities. Data collection techniques in this study used observation, interview, and documentation techniques. After collecting data in the field using observations, interviews, and documentation, then the data is recapitulated and analyzed. So it can be concluded that the application of yasin and tahlil activities in increasing religious values ​​at SMPS Al-Amin Bengkalis is in the Good category, this is indicated by the results of observations with the percentage of Yes as much as 81.4% and No as much as 18.5%. As for the supporting factors and inhibiting factors, the supporting factors are: SMPS Al-Amin Namely supported by students who are familiar with religious learning because after the completion of general learning at SMPS schools, in the afternoon students have cottage lessons which make students better understand religious lessons and also religious activities which will add insight or good Islamic values ​​to students. and inhibiting factors, namely: natural factors, if it rains, yasin and tahlil activities are not implemented